The Lost World : Jurassic Park #2 - Crichton, Michael, 1942-2008 (New York : Knopf, 1995)
On an island off Costa Rica there exists a hush-hush colony of giant animals which attracts the attention of two expeditions. The first one, including children, is led by a paleontologist, the other is made up of evil scientists who want to do experiments. The animals rout both without much concern for their motives.
Keywords: Dinosaurs -- Fiction; Cloning -- Fiction; Science fiction